Performance Analysis of γ-Radiation Test Monitor Using Monocrystalline n+pp++ Silicon Solar Cell: CsI(Tl) Scintillator - Ali Abd El-Salam Ibrahim; Mostafa Abd El-Fattah El-Aasser (Advances in Materials Science and Engineering)
The silicon solar cells are largely insensitive to gamma-radiation because the radiation passes through solar cells without imparting all of its energy. In order to enhance the sensitivity to radiation, the solar cells are coupled to CsI(Tl) scintillator. With the help of n+pp++ PESC monocrystalline silicon solar cells and CsI(Tl) scintillators, a gamma-radiation test monitor (TM) is developed. Due to safety concerns, a convenience relatively intense 60Co gamma-source is used as a suitable substitute for spent fuel. Two designs made of two representative arrays of monocrystalline solar cells are suggested. The induced current and voltage generated by these solar cells are measured. The temperature dependence of the induced current and the angular characteristic of the TM, for both designs, are presented. In comparison to conventional gamma-ray sensors, the Si solar cells exhibited better performance than the conventional types. Design II is found to be more efficient than I and superior performance for all of the measured parameters is obtained.